Inquiry, Expository and Motivation Learning Strategies on Pancasila and Civic Education Subjects Outcomes - Lely Verawati Br. Marbun; Deny Setiawan; Yakobus Ndona (Randwick International of Social Science Journal, 2023)
This research was carried out regarding the of Pancasila and civic education factuality subject outcomes or also called as PPKn is low, especially in class VII students due to the selection of inappropriate learning strategies. By choosing the right learning strategy, it is hoped that it will be able to provide understanding and interest in students so that learning motivation arises. This research to explain : 1) differences in PPKn subject outcomes for groups of students who were taught using inquiry and expository learning strategies, 2) differences in PPKn subject outcomes for groups of students who had high and low learning motivation, and 3). learning motivation in influencing PPKn subject outcomes. This research was conducted at SMP Negeri 3 Pulau Rakyat with a sample of class VII. The method used in this study is an experimental research method. The research design uses a 2x2 factorial design. There were two classes in this study, namely the experimental class with students in class VII-1 and the control class with students in class VII-4. The data collected are PPKn subject outcomes data and class VII students' learning motivation data. The results showed that 1) there was an influence of learning strategies in influencing PPKn subject outcomes with F count 58.775, 2) There was an influence of learning motivation in influencing PPKn subject outcomes with F count 92.04, and 3) there were interactions in learning strategies and learning motivation in affect learning outcomes PPKn with F count 4.09.